The numbers of sample design for evaluation of the soil fertility - Rozane, Danilo Eduardo [UNESP]; Romualdo, Liliane Maria; Centurion, José Frederico [UNESP]; Barbosa, José Carlos [UNESP] (Universidade Estadual de Londrina, 2011)
The determination of the amount of sample units that will compose the sample express the optimization of the workforce, and reduce errors inherent in the report of recommendation and evaluation of soil fertility. This study aimed to determine in three systems use and soil management, the numbers of units samples design, needed to form the composed sample, for evaluation of soil fertility. It was concluded that the number of sample units needed to compose the composed sample to determination the attributes of organic matter, pH, P, K, Ca, Mg, Al and H+Al and base saturation of soil vary by use and soil management and error acceptable to the mean estimate. For the same depth of collected, increasing the number of sample units, reduced the percentage error in estimating the average, allowing the recommendation of 14, 14 and 11 sample in management with native vegetation, pasture cultivation and corn, respectively, for a error 20% on the mean estimate.
Dimensionamento do número de amostras para avaliação da fertilidade do solo
Keywords: Corn; Horizontal variability; Native vegetation; Panicum; Soil simpling; Units samples